Expanding cryobanking assisted carp broodstock management for quality seed production - Kumar, Santosh; Kumar, Aditya; Sah, Rama Sankar (Indian Farming, 2023)
Quality seed is the most important input in the commercial freshwater aquaculture sector of the country and it is mostly supplied by hatcheries of the private and public sectors. With decades of hatchery-based carp culture and seed production intensification, a serious concern has emerged about seed quality, especially with the risks from inbreeding. Sperm cryobanking as a conservationtool, can not only provide support to captive breeding technology in the propagation-assisted rehabilitation of the target species in its natural habitat but can also assist carp broodstock management for quality seed production and sustainable fisheries and aquaculture enhancement. This report presents efforts and experiences of ICAR-NBFGR, Lucknow in customization of the sperm cryopreservation technique, primarily developed for ex-situ conservation, for upscaled fertilization through field validation, demonstrations, and capacity development of stakeholders in 11 states of the country.